1987
DOI: 10.1111/j.1469-7998.1987.tb01544.x
|View full text |Cite
|
Sign up to set email alerts
|

Weights of salivary glands in some ruminant animals

Abstract: The main paired salivary glands were dissected from Blackbuck, Chinese water deer, Reeves' muntjac and Red deer. The parotid glands, which have an important role in regulating ruminal digestion, were heaviest relative to body weight in the species (water deer and Muntjac) that naturally select the most digestible diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
28
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 6 publications
5
28
2
1
Order By: Relevance
“…These data and the data for 10 other African browsers extracted from their data list, and defined as browsers by having 10% or less grass in their diets, are shown in Table 3. They show that gland mass declines as body mass increases, and confirm that it correlates well with metabolic rate as proposed by Kay (1987) and Hofmann et al (2008). If so it will be small in large browsers.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…These data and the data for 10 other African browsers extracted from their data list, and defined as browsers by having 10% or less grass in their diets, are shown in Table 3. They show that gland mass declines as body mass increases, and confirm that it correlates well with metabolic rate as proposed by Kay (1987) and Hofmann et al (2008). If so it will be small in large browsers.…”
Section: Discussionsupporting
confidence: 64%
“…In giraffe it varies with browse height (Young & Isbell, 1991), bite size varies between 2.5 (Pellew, 1984B) to 0.5 grams per bite (Young & Isbell, 1991) and they take 15-30 bites a minute (Pellew, 1984A;Young & Isbell, 1991). Kay (1987) found that feeding increased secretion rate 4-fold in goats and Robbins et al (1995) measured a secretion rate of 3-16ml/gramDM intake in a browser. Applying these rates to giraffes, their parotid gland could secrete between 1.1±0.2 and 3.2±1.5 ml of saliva per gram of gland per minute while they are browsing (Table 2A).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to counteract plant secondary compounds, it has been suggested that BR produce salivary proteins that bind to these compounds. See Clauss (2003) and Shimada (2006) for reviews of species in which such proteins have been demonstrated; however, the number of species investigated thus far makes a statistical comparison between BR and GR unfeasible.Supposedly larger salivary glands of BR ruminants (Kay et al 1980;Kay 1987b;Hofmann 1988) have been considered to be a morphological correlate of a high production of these salivaryproteins ( Hypsodonty (as an adaptation to increased tooth wear due to abrasion and maybe increased attrition; C.3) has been observed in many GR groups such as marsupials, rodents, lagomorphs, and ungulates (Simpson 1953;Fortelius 1985;Janis and Fortelius 1988). Experimental work on the influence of crown height on survival is summarised in Williams and Kay (2001).…”
mentioning
confidence: 99%